Resolving Transnational Crime in the Indonesian Sea Border Area: Case Studies and Legal Effects - Sugeng Apriyanto; Fauzie Yusuf Hasibuan; Atma Suganda (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
The Indonesian maritime border area is susceptible to a range of transnational criminal activities, such as drug trafficking, human trafficking, and forced displacements. These criminal activities pose a significant danger to both the stability of national security and the territorial integrity and sovereignty of Indonesia. The law enforcement challenges in the Indonesian maritime border area are intricate, encompassing inter-agency coordination, international cooperation, and limitations in resources and technology. The primary objective of this study is to address the following crucial inquiry: What are the obstacles encountered in law enforcement against transnational crime at the maritime border of Indonesia? The study employs a normative legal research methodology, which entails analyzing legislative regulations, legal documents, and relevant literature that pertain to law enforcement along the maritime borders of Indonesia. This technique in normative jurisprudence will analyze applicable legal laws, government policies, and pertinent international agreements. The obtained secondary data from legitimate sources will undergo qualitative analysis to identify significant obstacles and possible remedies in law enforcement against transnational crime in the maritime border region of Indonesia. The study revealed that key hurdles in the enforcement of legislation against transnational crime in Indonesia's maritime border regions encompass inadequate inter-agency coordination, restricted resources and technology, and impediments to international collaboration. To tackle these challenges, it is advised that the Indonesian Government bolster regional and international collaboration, reinforce the capabilities of law enforcement agencies through training and the provision of cutting-edge technology, and establish a comprehensive and integrated policy framework. In addition, enhancing the formulation of comprehensive operational cooperation protocols and implementing efficient dispute resolution processes could enhance the efficacy of law enforcement in the maritime border region of Indonesia.